2009
DOI: 10.1055/s-0029-1210604
|View full text |Cite
|
Sign up to set email alerts
|

Two Independent Effects of Cortisol on Chicken Liver

Abstract: Activities of two key enzymes of glycogen metabolism have been measured after an acute administration of cortisol to 3d-old chickens. Glycogen synthase activity is enhanced 2-3 hours after a cortisol injection, and this activation is blocked by use of protein synthesis inhibitors. Glycogen phosphorylase activity is enhanced at an early stage, and this effect is not suppressed by protein synthesis inhibitors. Liver cAMP levels are not increased concomitantly with this early activation of glycogen phosphorylase;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This nuclear effect of glucocorticoids on the enzymes of glycogen metabolism has been recently documented by Hers (1985). However, in contrast with it, an early glycogenolytic effect, independent of protein synthesis enhancement, has been accounted (Egaña et al, 1981;Vallejo et al, 1986;Sancho et al, 1986), in animals treated with cortisol or other steroid hormones (Diez et al, 1984;Sánchez-Bueno et al, 1987). Dexamethasone, a synthetic analogue of cortisol, also elicits phosphorylase activation (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This nuclear effect of glucocorticoids on the enzymes of glycogen metabolism has been recently documented by Hers (1985). However, in contrast with it, an early glycogenolytic effect, independent of protein synthesis enhancement, has been accounted (Egaña et al, 1981;Vallejo et al, 1986;Sancho et al, 1986), in animals treated with cortisol or other steroid hormones (Diez et al, 1984;Sánchez-Bueno et al, 1987). Dexamethasone, a synthetic analogue of cortisol, also elicits phosphorylase activation (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…This effect is previous to the protein synthesis enhancement shown by the glucocorticoid between 2-3 h after hormone injection (Egaña et al, 1981;Vallejo et al, 1986). The event is due to an increase in glycogen mobilization associated to an activation of glycogen phosphorylase a; in addition, the liver cAMP levels falls and the cGMP levels increase (Sancho et al, 1986;Sánchez-Bueno et al, 1987). Recently, Prouva et al (1986) reported that 17ß-estradiol activates the transmethylating enzyme(s) involved in the conversion of PE to PC in ail subeellular fractions of pituitary membranes, mainly in endoplasmic reticulum and/or secretory granules.…”
Section: Introthictionmentioning
confidence: 99%
“…Studies from this laboratory have demonstrated that several steroid hormones display a glycogenolytic action, independent of their protein synthesis activation effects. Cortisol (Egafla et aL, 1981;Sancho et al, 1986;Vallejo et al, 1986), testosterone (Diez et al, 1984) and estradiol (Sanchez-Bueno et al, 1987) are able to activate liver glycogen phosphorylase without enhancing cAMP levels. However, cGMP levels are increased concomitantly or little after phosphorylase activation, cAMP levels are, on the other hand, significantly depleted.…”
Section: Introductionmentioning
confidence: 99%